1991
DOI: 10.1073/pnas.88.20.9302
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 expression is inducible by nerve growth factor in PC12 pheochromocytoma cells.

Abstract: Expression of the cytokine interleukin la (IL-la) was demonstrated in the rat PC12 pheochromocytoma cell line by (i) immunohistochemistry using rabbit polyclonal antisera raised against the recombinant murine IL-la, (it) an ELISA, and (i) a specific cell conversion bioassay based on the use of LBRM33-1A5 cells. IL-la mRNA was demonstrated in the PC12 cells, by PCR amplification. Constitutive expression of IL-la in PC12 cells was demonstrated in all experiments, although the cellular levels of IL-la-like immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 27 publications
(36 reference statements)
0
20
0
Order By: Relevance
“…In a series of elegant papers, Bartfai and colleagues [10,11] showed that adrenal chromaffin cells and a chromaffin-related line, PC 12 pheochromocytoma cells, are endowed with IL-1 producing ability in vitro. These authors also demonstrated that IL-1-like immunoreactivity in the adrenal medulla was associated with the IL-1· isoform, and estimated the amount of cytokine to be 50 pg/mg of adrenal gland protein [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of elegant papers, Bartfai and colleagues [10,11] showed that adrenal chromaffin cells and a chromaffin-related line, PC 12 pheochromocytoma cells, are endowed with IL-1 producing ability in vitro. These authors also demonstrated that IL-1-like immunoreactivity in the adrenal medulla was associated with the IL-1· isoform, and estimated the amount of cytokine to be 50 pg/mg of adrenal gland protein [15].…”
Section: Discussionmentioning
confidence: 99%
“…the chromaffin cells of the adrenal medulla, has also been reported [8][9][10]. In spite of extensive cellular and molecular characterization of IL-1 in different in vitro models of chromaffin cells [10,11], to our knowledge no study has thus far specifically investigated whether adrenal IL-1 plays a role in mediating HPA activation under stress conditions. Within this conceptual framework, the present study was established to investigate: (1) whether systemic IL-1 production undergoes significant changes in association with a physicoemotional type of stress, i.e.…”
Section: Introductionmentioning
confidence: 94%
“…NGF also directly stimulates degranulation of mast cells, increases the number of mast cells in peripheral tissues and promotes cell growth of myeloid cells (120,411,626), induces proliferation and differentiation of B cells, and enhances histamine release from basophils. NGF is also capable of stimulating IL-1 expression in PC12 cells and suppressing LTC 4 production in human eosinophils (13,846). Of note, NGF is upregulated in patients with atopic dermatitis, in which it may contribute to pruritus, mast cell stimulation, eosinophil activation, and keratinocyte dysfunction (reviewed in Refs.…”
Section: Ngf and Cutaneous Inflammationmentioning
confidence: 99%
“…Since NGF promotes the synthesis of IL-1β [24] and TNF-α gene activation [25], we tested the effect of NGFAb on carrageenan-induced joint inflammation. The results, shown in Fig.…”
Section: Influence Of Exogenous Administration Of Ngf Antibody On Carmentioning
confidence: 99%